2014
DOI: 10.1016/j.apsusc.2014.07.190
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chitosan–PEG binary template on the crystallite characteristics of sol–gel synthesized mesoporous nano-titania photocatalyst

Abstract: a b s t r a c tNano-titania is by far, the most studied material for its photocatalytic application in air and water pollution abatement. In this study, we have demonstrated the advantage offered by using a binary template of PEG and chitosan for the sol-gel synthesis of titania. Nano-titania samples were prepared using PEG, chitosan and the binary combination of these two as templates. XRD showed that all synthesized samples preserved the anatase structure. Titania sample prepared on 1% PEG and 3% chitosan as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…The results suggested that PEG was successfully conjugated to the CS. 32,33 Preparation and characterization of Peg-cs/sirNa nanoparticles Figure 4A shows that nanoparticles were obtained with PEG-CS complexing siRNA. The mean diameter of PEG-CS/ siRNA nanoparticles was 100 nm with the size distribution being relatively narrow.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…The results suggested that PEG was successfully conjugated to the CS. 32,33 Preparation and characterization of Peg-cs/sirNa nanoparticles Figure 4A shows that nanoparticles were obtained with PEG-CS complexing siRNA. The mean diameter of PEG-CS/ siRNA nanoparticles was 100 nm with the size distribution being relatively narrow.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…The IBP removal decreased from 98.6% to 76.8% when the initial concentration increased from 10 mg/L to 30 mg/L. The decrease can be ascribed to the saturation of the photocatalytic active sites by higher concentration of substrate and reduction the photons interaction [12,24]. Due to the saturation, the drug molecules cannot easily contact with the photo-induced holes of catalyst [25].…”
Section: Effect Of Catalyst Dosagementioning
confidence: 99%
“…Chitosan is a linear polysaccharide including amino and hydroxyl functional groups. Immobilizing TiO2 nanoparticles with chitosan could enhance the specific surface area and pore size [3,6,[9][10][11][12][13][14]. Zainal et al [3] showed that TiO2-Chitosan/Glass catalyst was efficient for removing monoazo dye via the combined effect of photocatalysis-adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the synthesis of mesoporous TiO2 materials is achieved using techniques including sol-gel (Antonelli and Ying 1995;Yang et al 1998;Gao et al 2007), microemulsion, and hydrothermal synthesis methods (Danumah et al 2001;Wang et al 2005;Wang et al 2007). Using surfactants as a template agent, self-assembly between organic and inorganic species can be generated (Preethi et al 2014).…”
Section: Introductionmentioning
confidence: 99%